The Role of Bacillus pseudomycoides Isolates and Bioinformatics Modeling for Modern Pharmaceutical Applications: A Literature Review - Ananta, Yorasakhi; Fitri, Salsabila Dwi (Dinasti Health and Pharmacy Science, 2025)
This article presents a literature review on the role of Bacillus pseudomycoides isolates as protease enzyme producers and how bioinformatics modeling enhances their potential in modern pharmaceutical applications. B. pseudomycoides is known to produce proteases with superior characteristics such as temperature and pH stability, making them potential candidates for pharmaceutical formulations. Bioinformatics approaches such as protein structure modeling, molecular docking, and genomic analysis have accelerated the functional characterization of these enzymes. The combination of the utilization of microorganisms and computational approaches opens up new opportunities in drug development, wound therapy, and pharmaceutical biotechnology. This study recommends multidisciplinary integration in the utilization of microbial resources for future therapeutic needs.